The history and professionalization of interpreting in Spain - Torres-Díaz, María Gracia (My University, 2015)
El trabajo está dedicado a la historia de la profesionalización del intérprete en España. 1.Sworn Translators and Interpreters. 2. Universities with courses on I/T. 3. Associations of I/T. 4. Other countries.
Keywords: Traducción - Historia - España; Legal interpreting; History of interpreting; Sworn interpreters